Pigmented Villonodular Synovitis of the Spine: Report of a Lumbar Case - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2009)
Pigmented villonodular synovitis is a benign proliferative disease of the synovial structures. This disease is most commonly seen in the extremities, and spinal involvement is extremely rare. In the relevant literature, 53 cases have been reported. We present a 66-year-old female patient with a long history of back pain, which progressed and radiated to the left leg over a period of 2 months. The patient also had a mass in the lumbar region on the grounds of spinal degenerative changes. Following gross total excision, the diagnosis was established by histopathology. In this report, we present our experience and discuss our neuroradiological and clinical findings.
Keywords: Pigmented villonodular synovitis; Spine; Vertebral spine tumor; GIANT-CELL TUMOR; CERVICAL-SPINE; TENOSYNOVITIS; DIAGNOSIS; FEATURES; JOINTS